Behavioural, Morphological And Chemical Strategies In Social Integrations Of Myrmecophilidae Crickets To Host Ants, Paratrechina Longicornis And Anoplolepis Gracilipes. - Ooi, Mark Chuan Sen (2021)
This thesis focusses on the integration strategies of ant crickets from the family Myrmecophilidae in colonies of invasive ants, Paratrechina longicornis (Latreille, 1802) and Anoplolepis gracilipes (Smith, 1857) (Hymenoptera: Formicidae) through behavioural, morphological, and chemical integration strategies.